An exploratory model on retirement savings behaviour: A Malaysian study - Nga, Joyce Koe Hwee * (Universiti Malaysia Sarawak, 2018)
Malaysia is expected to experience the ageing population problem by 2050, which is a cause for concern as Malaysians generally do not practice retirement savings behaviour. If Malaysians fail to address retirement planning early, then the burden of care may fall on their children and taxpayers in general. This study examines the retirement savings behaviour of 160 Malaysians through a multidisciplinary approach by concurrently investigating financial knowledge, quality of financial advisers, perception of health, and social influence as drivers of the behaviour. A conceptual framework is developed for these constructs, underpinned by various theories such as Theory of Planned Behaviour, Continuity Theory, and Social Identity Theory. All constructs, except quality of financial advisers, are found to have an influence on retirement savings behaviour. Financial knowledge is found to mediate the relationship between quality of financial advisers and retirement savings behaviour. Numerous implications from the study are discussed, such as the need for effective professional financial advisers and earlier intervention in financial education, long-term aged care, and other social security policy revisions.